Stabilisation of an isolated zygomatic arch fracture with a ballooned Foley catheter - Darren Wang; Ryan Smit; Belinda Liu; Cameron Lewis (Elsevier, 2022)
Zygomatic arch fractures have a potential for re-depression following surgery, which may necessitate the use of a splint to stabilise the reduction. An isolated zygomatic arch fracture reduced by Gillies temporal approach and stabilised by a ballooned Foley catheter is presented.